2006
DOI: 10.1007/11786986_47
|View full text |Cite
|
Sign up to set email alerts
|

Finite-State Dimension and Real Arithmetic

Abstract: We use entropy rates and Schur concavity to prove that, for every integer k ≥ 2, every nonzero rational number q, and every real number α, the base-k expansions of α, q + α, and qα all have the same finite-state dimension and the same finite-state strong dimension. This extends, and gives a new proof of, Wall's 1949 theorem stating that the sum or product of a nonzero rational number and a Borel normal number is always Borel normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…D. Doty, J. H. Lutz, and S. Nandakumar took a substantially different approach from D. D. Wall and strengthened his result. They proved in [Doty et al, 2007] that for every real number and every non-zero rational number the -ary expansions of , ( ), and ( ) all have the same finite-state dimension and the same finite-state strong dimension. It follows that and preserve -normality.…”
Section: Normality Preserving Functionsmentioning
confidence: 99%
“…D. Doty, J. H. Lutz, and S. Nandakumar took a substantially different approach from D. D. Wall and strengthened his result. They proved in [Doty et al, 2007] that for every real number and every non-zero rational number the -ary expansions of , ( ), and ( ) all have the same finite-state dimension and the same finite-state strong dimension. It follows that and preserve -normality.…”
Section: Normality Preserving Functionsmentioning
confidence: 99%
“…The question of how the complexity or measure theoretic properties of a real number are altered when it is transformed via a real-valued function goes back at least to Wall [14], who showed that adding or multiplying a nonzero rational number to a real number whose base-k expansion is normal 1 yields another real with a normal base-k expansion. Doty, Lutz, & Nandakumar recently extended Wall's result, showing that the finite-state dimension of the base-k expansion of a real number is preserved under addition or multiplication by a nonzero rational number [4]. At the other extreme of the complexity spectrum, it is not hard to show that algorithmic randomness (Martin-Löf randomness [13]) is preserved under addition or multiplication by a nonzero computable real, regardless of the base of the expansion.…”
Section: Introductionmentioning
confidence: 96%
“…This formulation, initially motivated by practical constraints, has proved to be rich and mathematically robust, having several equivalent characterizations. It has unexpected connections to areas such as number theory, information theory, and convex analysis [KN74], [DLN06]. Schnorr and Stimm [SS72] established a particularly significant connection by showing that a number is Borel normal in base b (see for example, [Niv56]) if and only if its base b expansion has finite-state compressibility equal to 1, i.e., is incompressible (see also: [BH13], [BHV05]).…”
Section: Introductionmentioning
confidence: 99%